Cracking Risk and Overall Stability Analysis of Xulong High Arch Dam: A Case Study - Peng Lin; Pengcheng Wei; Weihao Wang; Hongfei Huang (Applied Sciences, 2018)
It is of great significance to study the cracking risk, the overall stability, and the reinforcement measures of arch dams for ensuring long-term safety. In this study, the cracking types and factors of arch dams are summarized. By employing a nonlinear constitutive model relating to the yielding region, a fine three-dimensional finite element simulation of the Xulong arch dam is conducted. The results show that the dam cracking risk is localized around the outlets, the dam heel, and the left abutment. Five dam stress zones are proposed to analysis dam cracking state base of numerical results. It is recommended to use a shearing-resistance wall in the fault f57, replace the biotite enrichment zone with concrete and perform consolidation grouting or anchoring on the excavated exposed weak structural zone. Three safety factors of the Xulong arch dam are obtained, K_1 = 2~2.5; K_2 = 5; K_3 = 8.5, and the overall stability of the Xulong arch dam is guaranteed. This study demonstrates the significance of the cracking control of similar high arch dams.